UNDERSTANDING OF UNDERACHIEVER STUDENTS - ., Nurfaizal (JURNAL FOKUS KONSELING, 2016)
Good learning habit will determine students learning achievement. Underachiever students do not have good learning habit. They have characteristis for instance bad competence in doing school assignment, bad learning habit, having acceptance problem from their contemporary friends, having bad concentration in school activities, do not have self management both in the school and home, getting bored easily, leaving school activities, having good abiliy in spoken but not in written, no patient, busy with their mind, less honesty, frequently criticizing their self, having bad relationship with their friends, causing noise in the class. Thus, underachiever students have to be understood and assisted in order to develop maximally. Key Words: underachiever students.